Fourth Generation Outsourcing Ricardian Model on Indian Outsourcing Industry and Need For Next Generation Outsourcing - Wanchoo, Rajat (Prabandhan: Indian Journal of Management, 2010)
Outsourcing officially became a part of the business-dictionary during the 1980s. Even though the companies have been outsourcing work for many years, but this trend has been carried to an extreme level in the case of offshoring. People often use outsourcing and offshoring interchangeably, but there are important technical differences between them. Outsourcing involves contracting with a firm, individual or a supplier to do a specific task for which the client does not have talent, time, skill or efficiency of operation. Offshoring is a subset of outsourcing which specifically includes moving the organizational function outside of the home country, usually to take advantage of cheap labor and production.